The Impact of Covid-19 on Household Food Security and Income Generation in Mufulira District, Copperbelt Province (International Journal of Scientific Research and Management (IJSRM), 2022)
Household food security poses as a great challenge in most households especially in Africa. The ability to have sufficient food available at all times is deemed as a luxury. With the emergence of the Corona Virus disease commonly known as Covid-19, many countries have suffered economic recessions due to border closures, lockdowns, loss of human resource, diversion of funds hence leading to people losing their jobs, businesses going down and loss of family heads due to the virus. Therefore, this led to household food insecurity in most households and low-income generation. The purpose of the study was to investigate the impact of Covid-19 on household food security and income generation in Francis Mukuka, Mufulira District, Copperbelt Province. The specific objectives were to find out how Covid-19 has affected household food security, to examine the impact of Covid-19 on household income and to investigate measures put in place in order to cope with Covid-19. A case study research method that included a structured interview guide was used to collect data online from a sample of 26 respondents. The respondents were made up of those in employment and business owners, the married as well as those who are single. The study findings show that most households had challenges in feeding the family all the three meals required per day and they experienced inability to have all the desired food. They also revealed that people generated low income hence most of the respondents had to diversify into farming, doing part time business and looking for extra jobs. It was also found that, during the Covid-19 restriction measures, prices for goods had gone up, people were failing to purchase most things for their basic needs and those who could afford were buying in bulk because of restriction of movements. After the lifting up of Covid-19 measures, prices for goods have dropped. In view of the findings, the following recommendations were made. Increase the number of people on the Farmer Input Support Program (FISP) to increase agriculture production so as to achieve related sustainable development goals.